Angiogenic factors FGF2 and PDGF-BB synergistically promote murine tumor neovascularization and metastasis - Nissen, Lars Johan; Cao, Renhai; Hedlund, Eva-Maria; Wang, Zongwei; Zhao, Xing; Wetterskog, Daniel; Funa, Keiko; Bråkenhielm, Ebba; Cao, Yihai (The Journal of Clinical Investigation, 2007)
Tumors produce multiple growth factors, but little is known about the interplay between various angiogenic factors in promoting tumor angiogenesis, growth, and metastasis. Here we show that 2 angiogenic factors frequently upregulated in tumors, PDGF-BB and FGF2, synergistically promote tumor angiogenesis and pulmonary metastasis. Simultaneous overexpression of PDGF-BB and FGF2 in murine fibrosarcomas led to the formation of high-density primitive vascular plexuses, which were poorly coated with pericytes and VSMCs. Surprisingly, overexpression of PDGF-BB alone in tumor cells resulted in dissociation of VSMCs from tumor vessels and decreased recruitment of pericytes. In the absence of FGF2, capillary ECs lacked response to PDGF-BB. However, FGF2 triggers PDGFR-α and -β expression at the transcriptional level in ECs, which acquire hyperresponsiveness to PDGF-BB. Similarly, PDGF-BB–treated VSMCs become responsive to FGF2 stimulation via upregulation of FGF receptor 1 (FGFR1) promoter activity. These findings demonstrate that PDGF-BB and FGF2 reciprocally increase their EC and mural cell responses, leading to disorganized neovascularization and metastasis. Our data suggest that intervention of this non-VEGF reciprocal interaction loop for the tumor vasculature could be an important therapeutic target for the treatment of cancer and metastasis.